2006
DOI: 10.3732/ajb.93.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Ground layer carbon and nitrogen cycling and legume nitrogen inputs following fire in mixed pine forests

Abstract: Many mixed pine forests in the southeastern United States undergo prescribed burning to promote open pine savannas. In these systems, soil texture can influence fire's effect on vegetation and nutrient cycling. Our objectives were to examine fire and soil texture effects on carbon (C) and nitrogen (N) pools in ground layer vegetation. We measured biomass and tissue nutrient concentrations and estimated legume N inputs via N2 fixation in frequently burned sandy and clayey sites that were in the first and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…The 3-year post-fire treatment had the greatest amount of biomass production for Lupinus (and most other functional groups), but also the lowest amounts of available soil N. Although numerous studies have shown that tissue nutrient concentrations increase after fire (Anderson and Menges 1997;Bennett et al 2002;Rau et al 2008), studies examining response of legumes often find results similar to ours. Legume tissue N concentration was not affected by fire in pine forests, although other species did show an increase in tissue N concentrations (Lajeunesse et al 2006;Metzger et al 2006). In the present study, only Poa tissue concentrations followed a pattern that resembled that of available soil N, again suggesting that Lupinus is supplementing its N requirement through fixation of atmospheric N.…”
Section: Discussioncontrasting
confidence: 42%
“…The 3-year post-fire treatment had the greatest amount of biomass production for Lupinus (and most other functional groups), but also the lowest amounts of available soil N. Although numerous studies have shown that tissue nutrient concentrations increase after fire (Anderson and Menges 1997;Bennett et al 2002;Rau et al 2008), studies examining response of legumes often find results similar to ours. Legume tissue N concentration was not affected by fire in pine forests, although other species did show an increase in tissue N concentrations (Lajeunesse et al 2006;Metzger et al 2006). In the present study, only Poa tissue concentrations followed a pattern that resembled that of available soil N, again suggesting that Lupinus is supplementing its N requirement through fixation of atmospheric N.…”
Section: Discussioncontrasting
confidence: 42%
“…For example, C stocks at the reforested sites increased 80% from 1944 to 1999 (1.5%/yr), whereas N stocks increased 32% (0.6%/yr) over the same time frame. The slow accumulation of N may be due, in part, to the relatively minor input of N from N-fixing legumes on Fort Benning soils (LaJeunesse et al 2006) and/or a tightly closed N cycle in forests on the sandy, nutrient-poor soils. Finally, no significant differences in N stock in deeper soil layers (10-20, 20-30, and 30-40 cm) among reference forests, reforested, and disturbed sites indicate no strong effect of land use (either historic or contemporary) on soil N at these depths.…”
Section: Discussionmentioning
confidence: 99%
“…The question of how N is replenished following fire or timber harvest is poorly understood. Symbiotic Nfixing plant species are thought to be the main source of N following disturbance in temperate forest and grassland ecosystems; however, with extended periods of time without fire, the seedbanks of these species may be lost (Leach and Givnish, 1996;Newland and DeLuca, 2000) and many of these species rely on fire for regeneration (Casals et al, 2005;Hainds et al, 1999;Hendricks and Boring, 1999;Johnson et al, 2005;LaJeunesse et al, 2006;Towne and Knapp, 1996). The exclusion of fire from low elevation, dry montane forests in the western US may have increased the importance of free living N-fixing organisms colonizing mineral soil or decomposing woody roots (Chen and Hicks, 2003;Wei and Kimmins, 1998) in replenishing N losses following fire or harvest.…”
Section: Introductionmentioning
confidence: 99%